Documenta : Mythos und Wirklichkeit. - Kimpel, Harald (Köln : DuMont Buchverlag, 1997)
Arp, Hans (Jean) ; Bauer, Ingolf ; Beckmann, Max ; Ben ; Beuys, Joseph ; Bode, Arnold ; Borofsky, Jonathan ; Brandolini, Andreas ; Brock, Bazon ; Buren, Daniel ; Calder, Alexander ; Chagall, Marc ; Christo ; Close, Chuck ; Daem, Hilde ; Edoga, Mo ; Etienne-Martin ; Francis, Sam ; Geiger, Rupprecht ; Goldschmidt, Ernst ; Haacke, Hans ; Haring, Keith ; Haus-Rucker-Co ; Heisig, Bernhard ; Heuss, Theodor ; Immendorff, Jörg ; Indiana, Robert ; Isenrath, Hans-Paul ; Kienholz, Edward ; Kogler, Peter ; Kosuth, Joseph ; Kounellis, Jannis ; Kricke, Norbert ; Kriwet, Ferdinand ; Laurens, Henri ; LeWitt, Sol ; Lichtenstein, Roy ; Longo, Robert ; de Maria, Walter ; Mattheuer, Wolfgang ; Merz, Gerhard ; Merz, Mario ; Moore, Henry ; Nauman, Bruce ; Nay, Ernst Wilhelm ; Penck, A.R. ; Picasso, Pablo ; Richter, Gerhard ; Robbrecht, Paul ; Rosenbach, Ulrike ; Ruthenbeck, Reiner ; Schlemmer, Oskar ; Schütte, Thomas ; Sitte, Willi ; Trakas, George ; Tübke, Werner ; Vostell, Wolf ; Winter, Fritz ; Zadkine, Ossip
boek
Keywords: Kassel